If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (11x + 21) = (7x + 33) Reorder the terms: (21 + 11x) = (7x + 33) Remove parenthesis around (21 + 11x) 21 + 11x = (7x + 33) Reorder the terms: 21 + 11x = (33 + 7x) Remove parenthesis around (33 + 7x) 21 + 11x = 33 + 7x Solving 21 + 11x = 33 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 21 + 11x + -7x = 33 + 7x + -7x Combine like terms: 11x + -7x = 4x 21 + 4x = 33 + 7x + -7x Combine like terms: 7x + -7x = 0 21 + 4x = 33 + 0 21 + 4x = 33 Add '-21' to each side of the equation. 21 + -21 + 4x = 33 + -21 Combine like terms: 21 + -21 = 0 0 + 4x = 33 + -21 4x = 33 + -21 Combine like terms: 33 + -21 = 12 4x = 12 Divide each side by '4'. x = 3 Simplifying x = 3
| x+(x+2)=790 | | -9(2)= | | 5(x+4)=3(x+20) | | 2x^2+20x-24=0 | | 2(x-7)=64 | | 5*(2x+3)=8x-6 | | 10x+8-5x-3=85 | | 42p^2-85p+42=0 | | 5(x+4)=90 | | 7xy+2y^2=0 | | -t^2+4=0 | | 5x^2-36w=32 | | 4x+6+6x+8=94 | | -1x+4y=4 | | e-t^2+4=0 | | 2x+3+3x+7=75 | | 3(2x-1)-2(2x-4)=19 | | 7(3x-13)=161 | | 8x-7+2x-5=58 | | 16(x-4)=13(x-5) | | 1-2(-2)+3(-5)= | | x-2*3+x-2*2=25 | | -6(-4u+7)-2u=7(u-3)-3 | | 4x+8-2x+7=39 | | e^8=y | | 11x+17=5x-19 | | 2x+86=13 | | 2x+5+x+2=25 | | 8-2m-m^2=0 | | x^2-50x-75=0 | | 2(j-10)=10 | | F(x)=100x-5x^2 |